Enseignement et pédagogie dans les académies protestantes au xviie siècle - Guy Astoul (Les Cahiers de Framespa)
In the kingdom of France, academies were established, just like in Geneva, to train the future ministers of the reformed Churches. Associated with existing colleges, these academies gave priority to theological training and to in-depth study of the Sacred texts in their original languages. The teaching of Greek and Hebrew was considered essential and performed by specialized professors. Such establishments resulting from the Reform and its humanistic heritage wanted to renew the teaching methods and contents. By studying the teaching provided in these academies and the contents of the courses, it is possible to compare the pedagogy which prevailed in these institutions, although their practices can be different according to the city, be they located in the kingdom at Montauban, Nimes, Saumur, Die, or on its margins like Orthez or Sedan.